[NEMI report on indoor air quality] (Tufts Archival Research Center, 2007)
Report on Indoor Air Quality by NEMI for the Labor Management Committee in August 1997. Divided into several catergoies, including marketing, special projects and program planning and admistration among others. Contains a list of activities already undertaken and activities planned for each section. Concludes with a budget for the whole project.